Clinical Determinants Associated With Viral Load Count Among Adult TB/HIV Co-Infected Patients: A Linear Mixed-Effects Model Analysis - Nurye Seid Muhie; Habib Mohammed Yimam; Awoke Seyoum Tegegne; Abdela Assefa Bekele (Advances in Virology)
HIV is a major cause of tuberculosis. The objective of current study was to isolate clinical determinants associated with viral load count among adult TB/HIV co-infected patients. This study was done at the University of Gondar Comprehensive Specialized Hospital from March 2017 to March 2022. In this study, linear mixed-effects models were used for repeated measure viral load count. Results from the analysis show that baseline viral load count (β=465.1, p value = 0.0026), hemoglobin levels (β=−493.5, p value = 0.0107), CD4 cell count (β=−38.2, p value = 0.0027), CPT (β=−326.8, p value = 0.0363), functional status (β=416.0, p value = 0.0059), OCC (β=123.0, p value = 0.0028), tuberculosis type (β=430.3, p value = 0.0336), platelet cell count (β=−2.5, p−value=0.0005), lymphocyte count (β=−7.9, p value = 0.0219), and visit time (β=−2.2, p value = 0.001) were clinical determinants that affected repeated measure viral load count at a 5% level of significance. The study examined clinical determinants of repeated measure viral load count among TB/HIV co-infected patients. The clinical determinants like hemoglobin levels ≥ 11 g/dL, CD4 cell count ≥ 200 cell/mm3, CPT drug users, and platelet cell count, lymphocyte count, and visit time were decreased viral load count. Inversely, baseline viral load count (≥ 10,000 copies/mL), bedridden patients, patients with OCC, and those with extrapulmonary tuberculosis had a higher viral load count. Extensive monitoring and counseling can be beneficial for patients with hemoglobin, CD4 cell count, CPT, platelet cell count, lymphocyte count, visit time, baseline viral load count, and functional status, OCC, and TB type. Finally, further studies should be done in order to address major clinical determinants and enhance continuous follow-ups, monitor TB/HIV progression, and improve the life expectancy of patients living with TB/HIV.